The Effectiveness of Directed Drilling Track Planning Method with Variation of Build Up Rate - Stevy Canny Louhenapessy; Randa Putra Jusmal Melato (Jurusan Teknologi Produksi dan Industri, Institut Teknologi Sumatera, 2023)
The build-up rate test in this case study was carried out using three BUR variables, namely 30/100 ft, 50/100 ft, and 70/100 ft, which were simulated using the directional drilling trajectory method. The results of each BUR obtained when using the build and hold drilling trajectory method resulted in a maximum inclination angle of 39.1970, 31.8540, and 30.0930; the vertical section depth to the end of the build were 1707.02 ft, 1104.77 ft and 910.41 ft; the measured depths to the end of the build were 1807 ft, 1137 ft, and 930 ft; and the measured depths to the target point were 2584 ft, 2556 ft, and 2547 ft. While the results of each BUR obtained when using the buildup drilling trajectory method resulted in a maximum inclination angle of 56,680, 76,2890 and 95.5620; the vertical section depth to the end of the build of 2269.92 ft, 2298.22 ft and 2311.95 ft; measured depths to the end of the build of 2563 ft, 2711 ft and 2886 ft; and the measured depth to the target point were 2636 ft, 2759 ft and 2886 ft. BUR comparisons performed on these two methods have advantages and disadvantages in terms of the analyzed parameters. This parameter can affect drilling risk, drilling time efficiency, and economy